Bifunctional Bi12O17Cl2/MIL-100(Fe) composites toward photocatalytic Cr(VI) sequestration and activation of persulfate for bisphenol A degradation - Chen Zhao; Jiasheng Wang; Xi Chen; Zhihua Wang; Ji, Haodong; Long Chen; Liu, Wen; Chong-Chen Wang (Science of The Total Environment, 2021)
Bifunctional Bi12O17Cl2/MIL-100(Fe) composite (BMx) was firstly constructed via facile ball-milling method. The optimal BM200 was highly efficient for Cr(VI) sequestration and activation of persulfate (PS) for bisphenol A (BPA) decomposition under white light illumination, which was much more remarkable than the pristine MIL-100(Fe) and Bi12O17Cl2, respectively. Furthermore, the photocatalytic reduction efficiency can be significantly improved via the addition of some green small organic acids (SOAs). As well, the BPA degradation can be achieved over an extensive initial pH range of 3.0–11.0. When the PS concentration increased to more than 2.0 mM, the BPA degradation efficiency decreased due to the SO4−• self-scavenging effect. It was also found that the co-existence of inorganic anions like H2PO4−, HCO3−, SO42−, Cl− and NO3− could decelerate the BPA degradation. The excellent photocatalytic Cr(VI) reduction and persulfate activation performances originated from both MIL-100(Fe) with excellent PS activation ability and Bi12O17Cl2 with a favorable band position, which not only enabled the efficient separation of charges but also accelerated the formation of SO4−• radicals. The BM200 displayed prominent stability and recyclability. More importantly, the credible degradation pathway was proposed based on UHPLC-MS analysis and DFT calculation. This research revealed that the Fe-based MOFs/bismuth-rich bismuth oxyhalides (BixOyXz, X = Cl, Br and I) composites possessed great potential in wastewater remediation.
Keywords: BiOCl; Bisphenol A; Cr(VI); Metal-organic frameworks; Persulfate